Best-before date – food storage temperatures recorded by Swedish students. Issue 6 (8th June 2015) - Marklinder, Ingela; Eriksson, Mattias K
Abstract : Purpose: – The purpose of this paper is to investigate the food storage temperature in Swedish household refrigerators, to determine whether students use the best-before-date label to determine food edibility, and to examine if the study increased the students' interest and knowledge regarding these issues. Design/methodology/approach: – In total, 1, 812 students, enrolled at 72 Swedish schools, analysed the temperature on different shelves in their family refrigerator using thermometers (Moller-Therm (+0.5/−0.1 °C) and instructions provided by their teachers. A questionnaire dealing with the issues of date labelling, food safety, refrigerator storage and food wastage was completed by the teachers. Findings: – The temperature at the back of middle shelves was coldest (average 4.8 °C; SD 3.1). A relatively high proportion of food items were stored at higher temperatures than recommended. The use-by date had been exceeded for 30 per cent of products, but the students did not rate these as inedible. According to the teachers, the investigation increased interest and knowledge among their students of date labelling, food hygiene, refrigerator storage and food waste. Research limitations/implications: – Thermometers were used to measure air temperature on different shelves in the family refrigerator. Data collection was not controllable, as the students measured without supervision. Practical implications: – The teachers reported that the study increased interest and knowledge among their students regarding cold food storage. Social implications: – This way of teaching food safety would meet the aim of generally increasing food safety knowledge in society, which might have a positive impact on public health. Originality/value: – The use of school-children as data collectors to determine refrigerator temperatures in private homes is a novel approach, which was an efficient way of teaching relevant facts as well as collecting large amounts of data.